ANALISIS REKRUTMEN DAN SELEKSI KARYAWAN DI KLINIK ALRASHA HEALTH CARE CENTER TANJUNGPINANG - Muhammad Rizki; Eko Harsoyo; Agustinus Sihombing; Fatahuddin, Fatahuddin (Juremi: Jurnal Riset Ekonomi, 2024)
The purpose of this research is to find out how employees are recruited at the Alrasha Health Care Center Tanjungpinang Clinic and to find out how employees are selected at the Alrasha Health Care Center Tanjungpinang Clinic. This study had a sample of 7 people who were determined using a sampling technique, namely purposive sampling. The method used in this research is a qualitative research method. The research object is the Alrasha Health Care Center Clinic. The data used is primary data. Data processing techniques use data reduction, data presentation and drawing conclusions. The results of this research show that the Alrasha Health Care Center Clinic uses a Manpower Needs Analysis as a basis for employee recruitment at the Alrasha clinic. Recruitment also looks at financial adequacy and clinic financial funding. The source of employee recruitment at the Alrasha clinic uses internal sources and external sources. The recruitment methods used are open methods and closed methods and in the selection process experience is one of the benchmarks for whether or not a candidate is accepted or not. The next selection process is a written test for prospective applicants to complete 50 questions. The questions contain multiple choice questions and essay questions. I was given 60 minutes. The interview process used by the Alrasha Health Care Center clinic is Structured and Unstructured Interviews